Comparing the performance of the biathlon rifles with wooden and titanium frames - Koptyug, A.; Bäckström, M.; Olsson, V. (Proceedings, 2020)
The present paper describes preliminary results of studies carried out using a new measurement setup and a biathlon rifle with two different interchangeable stocks: a commercial, mainly wooden one and one additively manufactured from titanium alloy and a polymer PA 2200, employing lightweight, 3D lattice architecture. A finite element analysis of the predicted mechanical properties of new design elements was carried out prior to the manufacturing. Experiments were carried out using a novel setup for the assessment of athlete and rifle performance in biathlon shooting. Data acquisition was carried out at the rates of few kilosamples per second, using a combination of an airbag-based rifle butt pressure sensor, a trigger loading sensor, strap load cell, and two tri-axis MEMS sensors—an accelerometer and a gyroscope. All tests indicate that a rifle stock additively manufactured from titanium alloy could provide better recoil damping compared to the commercial, mainly wooden one. Together with the high capacity of additive manufacturing technologies in equipment individualization, this may provide additional possibilities for the improvement of sports rifle construction and help athletes achieve better results in competitions.